An Investigation Of Students’ Attitude Towards Learning Mathematics In Digital And Traditional Classroom : A Study Of Secondary Students In Guwahati City - Devajit Sarmah, Gunendra Chandra Das (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The attitude of secondary students can be influenced by the teacher's attitude, personality, and teaching approach in the classroom. The success of students in mathematics is determined by their positive attitude toward the topic, the teachers' teaching approaches, and the school environment. The purpose of the study was to find out how students feel about learning mathematics in both digital and traditional classrooms. The research is based on a survey of secondary school students (9th grade) in Guwahati city from both the government and private sectors that includes students of both genders. The study included a sample of 400 students (digital classroom-186, traditional classroom-214) from both government and private institutions. A 5-point likert scale questionnaire comprising 20 items (alpha=0.799) was utilised to collect data from the respondents to investigate the attitude of students after they had been validated and their reliability verified . Means, standard deviation, t-test, and correlation were used to analyse the data. This study found that digital learning has a greater impact on students' attitudes than traditional classroom education, in case of both male and female students, government and private, SEBA and CBSE.